ETIKA PROFESIONALITAS TENAGA PENDIDIK SEKOLAH PAUD INKLUSI TERPADU BINA CERIA - Restu Rahmanita Sekaring Putri; Sayidatul Maslahah (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2022)
As an educator, it is important to understand the ethics of professionalism as an educator, because it is not only teaching students to be smart students. But an educator also controls education and becomes an example for his students to imitate, especially since Law no. 20 of 2003 concerning the national education system, special education or can be called special education that handles students who have special differences with other students out there. However, in carrying out their duties, educators will sometimes encounter obstacles that can hinder the teaching process of children. Because it is important from an early age to know how the ethics in the professionalism of an educator in special schools or can be called inclusive schools or ABK schools (children with special needs), so that prospective educators, especially educators in inclusive schools, clearly understand their role and apply their ethics professionalism in teaching. Because by knowing the professional ethics of an educator, it is hoped that the quality of educators in Indonesia can be better so that it gives birth to students who excel and have good character and behavior, besides that, educators must clearly understand that the task of educators is to maintain the good name of the school, harmony between students and educators. In addition, an understanding of the concept of professional ethics for education personnel includes an understanding of educational staff, the types of educators, an understanding of ethics, and the purpose of ethics that must be understood by educational staff.